Organization of human replicon: singles or zipping couples? - Ligasová, Anna; Raska, Ivan; Koberna, Karel (Journal of structural biology, 2009)
According to a general paradigm, proper DNA duplication from each replication origin is ensured by two protein complexes termed replisomes. In prokaryotes and in budding yeast Saccharomyces cerevisiae, these two replisomes seem to be associated with one another until DNA replication initiated from the origin has finished. This arrangement results in the formation of the loop of newly synthesized DNA. However, arrangement of replisomes in other eukaryotic organisms including vertebrate cells is largely unknown. Here, we used in vivo labeling of DNA segments in combination with the electron microscopy tomography to describe the organization of replisomes in human HeLa cells. The experiments were devised in order to distinguish between a model of independent replisomes and a model of replisome couples. The comparative analysis of short segments of replicons labeled in pulse-chase experiments of various length shows that replisomes in HeLa cells are organized into the couples during DNA replication. Moreover, our data enabled to suggest a new model of the organization of replicated DNA. According to this model, replisome couples produce loop with the associated arms in the form of four tightly associated 30nm fibers.
Keywords: chromatin; HeLa Cells; Replicon; Electron Microscope Tomography; Deoxyuracil Nucleotides; počítačové zpracování obrazu; replikon; Humans; Multienzyme Complexes; Cell Nucleus; Nucleic Acid Conformation; buněčné jádro; multienzymové komplexy; bromodeoxyuridin; DNA-Directed DNA Polymerase; Image Processing, Computer-Assisted; replikace DNA; lidé; deoxyuracilnukleotidy; modely genetické; Bromodeoxyuridine; DNA Replication; Models, Genetic; HeLa buňky; Chromatin; konformace nukleové kyseliny; DNA-dependentní DNA-polymerasy; tomografie elektronová